2018
DOI: 10.1016/j.molmet.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences underlying pancreatic islet biology and its dysfunction

Abstract: BackgroundThe sex of an individual affects glucose homeostasis and the pathophysiology, incidence, and prevalence of diabetes as well as the response to therapy.Scope of the reviewThis review focuses on clinical and experimental sex differences in islet cell biology and dysfunction during development and in adulthood in human and animal models. We discuss sex differences in β-cell and α-cell function, heterogeneity, and dysfunction. We cover sex differences in communication between gonads and islets and islet-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 114 publications
(145 reference statements)
8
99
1
Order By: Relevance
“…Sex specific differences in alpha and beta cell identity and function. Glucose homeostasis is maintained differently between men and women (Anderwald et al, 2011;Basu et al, 2006;Faerch et al, 2010;Gannon et al, 2018). Although both sexes have similar peripheral insulin sensitivity, women have lower levels of endogenous glucose production, lower fasting plasma glucose concentrations, and higher glucose levels ~2 hours after delivery of an oral bolus of glucose (Anderwald et al, 2011;Basu et al, 2006;Faerch et al, 2010;Gannon et al, 2018).…”
Section: Reconfiguration Of the Human Delta Cell Population In T2d Ismentioning
confidence: 99%
“…Sex specific differences in alpha and beta cell identity and function. Glucose homeostasis is maintained differently between men and women (Anderwald et al, 2011;Basu et al, 2006;Faerch et al, 2010;Gannon et al, 2018). Although both sexes have similar peripheral insulin sensitivity, women have lower levels of endogenous glucose production, lower fasting plasma glucose concentrations, and higher glucose levels ~2 hours after delivery of an oral bolus of glucose (Anderwald et al, 2011;Basu et al, 2006;Faerch et al, 2010;Gannon et al, 2018).…”
Section: Reconfiguration Of the Human Delta Cell Population In T2d Ismentioning
confidence: 99%
“…This is reflected by lower blood glucose and higher serum insulin levels 30 minutes after glucose administration during and IPGTT. Therefore, although these islets are being "overworked" from a young age, they appear to have protective 12 mechanisms in place to cope with the demands of increasing adiposity and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Females appear to be protected from β-cell death in most rodent models of T2D [12,20]. In the case of exposure to maternal diet-induced obesity/high fat-feeding and future T2D risk in the offspring, Yokomizo and colleagues showed that islets from female offspring were better to able to compensate and adapt to a high fat diet (HFD) in postnatal life compared to male offspring [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations